Next-generation T cell immunotherapy: overcoming exhaustion, senescence, and suppression - Li, Guangmei; Li, Dengju; Zhu, Xiaojian (Frontiers in immunology, 2025)
T-cells are a core component of tumor immunotherapy because of their potent ability to identify and kill cancer cells. Yet efficacy is limited by exhaustion, senescence, metabolic dysregulation, an immunosuppressive tumor microenvironment (TME), and limited persistence. This review analyzed these key issues and proposed targeted improvement strategies. Emerging approaches encompass pharmacological modulation of T cell activation and survival pathways, epigenetic reprogramming to reverse exhaustion and senescence, metabolic engineering, combinatorial targeting of immunosuppressive TME components and advanced genetic tools, notably CRISPR-Cas9–based CAR-T optimization, which exemplifies how precise genome editing can enhance therapeutic efficacy. We review the progress and prospects of T-cell improvement strategies in tumor immunotherapy, emphasizing the need for further exploration to enhance the broader application and long-term efficacy of T-cell therapies. This review highlights recent advances and future directions in T-cell engineering, metabolic modulation, and microenvironment targeting, aiming to translate innovations into effective cancer immunotherapies.